The reality of employing educational technologies in teaching students with disabilities from the point of view of teachers of special education - Aldhafeeri, Abdulrahman Khalaf (Journal of Educational and Psychological Sciences, 2023)
The study aimed to reveal the reality of employing educational techniques in teaching students with disabilities from the point of view of teachers of special education. The study followed the descriptive approach. The sample consisted of all male and female teachers of special education programs in the academic year 1443 AH - 2022 AD, including a number of (279) male and female teachers. The study sample consisted of (155) male and female teachers who responded to the demanded questionnaire. The study data were collected using a questionnaire specially designed for the purpose of the study. The results showed that there is a high level of reality of the use of educational technologies by special education teachers in special education programs, in addition , it refered that one of the basic obstacles that prevents the use of educational technologies is the difficulty of taking into account the characteristics of special education categories when choosing educational technologies in explaining the lesson. The study also recorded the absence of a statistically significant difference in the response of male and female teachers due to the gender variable; Except for the axis of administrative and technical obstacles, in favor of female teachers